Severe virus associated community acquired pneumonia: predictors of lethality - Pertseva, T. O.; Kireyeva, T. V.; Bielosludtseva, K. O.; Boltyanskiy, S. V.; Nazarenko, O. P. (Zaporozhye Medical Journal, 2016)
Despite the fact that the influenza virus pathogenicity factors have been well studied in vitro, in vivo lack is presented in understanding of the those risk factors, objective and laboratory parameters, which related most of all to the fatal virus-associated community-aquired pneumonia (CAP). That is why the purpose of the study was to study the clinical and laboratory characteristics of patients with severe virus-associated CAP during the 2015–2016 influenza epidemic and their role as predictors of patients’ mortality. To do this, patients with severe virus-associated CAP were examined. They were divided into 2 groups depending on the outcome of treatment: 1st- deaths from the virus-associated severe CAP and 2nd - patients with successful treatment of the severe virus-associated CAP. Special statistical method was used – one-dimensional analysis of variance to compare individual parameters between the two groups of patients (surviving and deceased). Pearson χ2 test (contingency table) was used for categorical variables. Factors that were significant predictors of mortality as a result of univariate analysis were tested using multifactorial analysis using logistic regression. In the final model, each parameter must have had a significant impact on mortality. It was found that risk factors for death in patients with severe virus-associated CAP according to univariate analysis were: presence of obesity, disorders of consciousness, BH≥35 min, SaO2<80%, PaO2<50 mm Hg, mmHg PaCO2 ≥50 mmHg during hospitalization. Independent predictors of mortality according to the logistic regression are the presence of obesity, disorders of consciousness, PaO2<50 mm Hg, mmHg PaCO2 ≥50 mmHg. Given that among clinical and laboratory parameters key parameters that significantly influence the outcome, are indicators of the severity of hypoxia and hypoxemia, a major step in determining the severity of the patients with virus-associated severe emergency is diagnostics of blood gas composition, and during treatment – early sufficient and adequate oxygen therapy with regular monitoring of its effectiveness and timely correction.